Affordable graphics cards for builders on a budget. - Allardo, Billy Joe I.
An article featuring Axle Tornado 8500GT 1GB DDR2 and Axle Tornado 8600GT 512MB GDDR2, efficient yet cheap video cards.
Keywords: Computers--video cards